The Effect of RGEC on Financial Distress in Islamic Commercial Banks - Puput Fitriana; Darmawati; Angrum Pratiwi (Fakultas Ekonomi dan Bisnis Islam, UIN Sunan Kalijaga Yogyakarta, 2022)
A bank's ability to grow depends on its ability to raise funds. If the bank does not have sufficient funds, the bank will face various risks, including liquidity risk or even financial difficulties. Businesses need to reduce the risk of financial distress and understand the elements that drive it. The purpose of this study was to examine the effect of Risk Profile, Good Coorporate Government, Earnings, and Capital (RGEC) on financial distress at Indonesian Islamic Banks. Associative descriptive quantitative methodology was used in this study. With secondary data from Islamic commercial banks in Indonesia, namely annual financial reports and GCG reports for the 2015-2020 period. Purposive sampling was used to select 9 out of 14 Islamic commercial banks in Indonesia. The independent variables are NPF, FDR, GCG, ROA, ROE, CAR, and the dependent variable is financial distress, which is calculated using the Altman Z-Score model. Using multiple linear regression analysis. The results show that NPF has a significant negative effect on financial distress, while FDR has a significant positive effect on financial distress, while GCG, ROA, ROE, and CAR have no significant effect.